Evaluating the Cost and Schedule Risk of Tidal Energy Projects (Proceedings of the European Wave and Tidal Energy Conference, 2025)
It is well documented that the ability to determine the cumulative impact of risk using traditional methods is prone to a large number of bias (Flyvbjerg 2018, Kahnemann, 2011).This is particularly significant when trying to forecast the likely cost and schedule of innovative and unusual projects such as Tidal Energy Projects.Alternative ‘external’ methods such as Reference Class Forecasting are now widely accepted as providing more realistic forecasts (Flyvbjerg, 2020).As there are few completed Tidal Energy projects which could generate a whole-project Reference Class, the technique is adapted to recognize that many of the individual components are well-established; such as civil works, marine works, pre-casting caissons and mechanical and electrical activities.Oxford Global Projects utilized this approach on a Tidal Energy Project under development in the UK and was able to draw on over 4000 datapoints to generate both cost and schedule forecasts.The analysis illustrates that the risk associated with Tidal Energy Projects is statistically similar to many more familiar mega-projects such as ports, harbours and large civil engineering projects and notably lower than other forms of low-carbon energy production. It also highlights the key aspects of these projects which do merit further attention to reduce risk, many of which are not the physical ability to deliver the project but the political, socio-economic and regulatory frameworks which enable them.Tidal Energy Projects can make a significant contribution to the global pursuit of net zero – as well as ancillary benefits for flood protection. Demonstrating a robust, quantified and tolerable risk profile with confidence levels in budget and schedule milestones plays a vital assurance role and securing the support and commitment from governments, funders and the public.This Paper will illustrate the simplicity of the methodology adopted, the outcomes on the pilot project and the benefit of augmenting more traditional risk management processes with Reference Class Forecasting.It will also discuss an opportunity for the Tidal Energy community to collaborate in data sharing and the benchmarking of cost and schedule for projects.